Estimating biomass sources for a 10 MW dendro power plant using Leucaena leucocephala fuel wood - Muhamad, Mohd Izhwan; Mohd Radzi, Mohd Amran; Othman, Mohammad Lutfi; Hizam, Hashim; Gomes, Chandima; Alias, Mohamad Azani (IEEE, 2023)
This paper presents the results of an investigation to determine the potential of Leucaena leucocephala as a commercial energy crop for dendro-power generation plants. Dendro-power generation is the generation of electricity from wood fuels. Modern technology enables the efficient, clean and long-term use of wood in dendro power plants. Various tests and calculations have been carried out, such as moisture content, physical analysis and calorific value of tree species. The Leucaena leucocephala yield per unit area of the special plantation for the development of 10 MW dendro power plants was estimated. The development of a 10 MW dendro power plant provides for an annual electricity generation of 50 GWh, which can be used for self-consumption or sold to a power company. This study provides a quantitative approach to estimating the wood requirements for Dendro power generation which has not been done before. From the calculation, the annual fuel consumption of the Dendro power plant requires 48,880 tons/year. Therefore, the total area required for planting the energy plant Leucaena leucocephala is 815 hectares. The number of Leucaena leucocephala trees required to meet the annual fuel consumption of the Dendro power plant is 4,075,000 trees. The implementation of this project will also help the economic development of local communities, especially in rural areas.